IMPROVED FINITE ELEMENT TRANSFER MATRIX METHOD OF PLANE BEAM ELEMENTS USING THE ABSOLUTE NODAL COORDINATE FORMULATION - QIAN ShuangLin; HE Bin; YAO LiKe; NI ChunHai; LV JianDong (Jixie qiangdu)
For the dynamics problems of flexible beams with large overall motion,nonlinear element dynamic equations are established,adopting the absolute nodal coordinate formulation（ ANCF）. Since the relationship of generalized accelerations and generalized forces is linear in the equations,a new absolute nodal acceleration finite element transfer matrix method（ TMM） for plane beam is proposed,combining the idea of TMM. Compared with traditional finite element transfer matrix method,transfer matrixes of the proposed method are derived without time-integration methods. Here ordinary differential equation numerical methods can be applied conveniently. Finally,the method is verified correct by an example,the beam with large overall motion and small deformation.